Soft tissue injuries: 3. Paraspinal. Issue 8 (25th July 2008) - Timothy, J; Foley, E; Comer, C; Barron, D; Sloan, J; Shilliday, H
Abstract : A review of injuries to the spinal musculature, spinal ligaments, intervertebral discs, zygapophyseal joints (facet joints) and nerve roots.